Neurocognitive recovery of patients with paranoid schizophrenia - Molchanova, Olena (Psychosomatic Medicine and General Practice, 2017)
Background. At present neurocognitive impairment is considered a core feature of schizophrenia. This statement is grounded on cognitive impairment stability, the persistence of cognitive impairment independently of the disease stage and other symptoms of schizophrenia. The relevance of the search for cognitive remediation methods is determined by the influence of cognitive functioning on the functional outcome in patients with schizophrenia. In order to solve this problem, scientists are actively investigating such direction in the treatment of patients with this psychopathology as «neurocognitive therapy» or neurocognitive training. Objective.To evaluate the effectiveness of neurocognitive training in patients with paranoid schizophrenia. Methods and materials. The patients who matched inclusion criteria were assessed on Positive and Negative Syndrome Scale (PANSS), Personal and Social Performance scale (PSP), neuropsychological tests (Trail Making Test part A and B, Wisconsin Card Sorting Test, Luria test) at the baseline, 1st and 6th month. All patients who were included in the study were randomly assigned into two groups. The intervention group (n=40) underwent a standard supportive treatment and neurocognitive training. The control group (n=31) received supportive medication treatment alone. Results. After 1st month, a statistically significant difference between the intervention and control groups was found both for the overall PANSS score improvement and improvement in several items, which represented the cognitive decline. Total PSP score increased significantly in the intervention group from 41-50 to 51-60 (р=0.0001). In Wisconsin Card Sorting Test the proportion of incorrect answers decreased by 31.4% (р=0.0001), perseverative errors by 20.1% (р=0.042), the number of completed categories increased by 33.5% (р=0.002). Conclusion. The proposed neurocognitive training program showed positive results, which was reflected in a statistically significant improvement in PANSS score and cognitive tests performance in the intervention group compared to control group after treatment course and additional 5 months of the observation.